Diets, food and idiopathic parkinson`s disease (2014)
Based on two individual cases, this is a personal depicton knowledge of Idiopathic Parkinson´s Disease (IPD)etiopathogeny emphasizing diets, food and edible substancestested and reported. In the first case (adherence to an almostvegan diet, with one seventh of the protein supplied fromanimal origin), had an impressive beneficial effect onhis fifteen years clinical course, while in the second case(continuation of a quasi ovo-lacto-vegetarian diet), did notmodify substantially the clinical course. The relevance of dieton IPD focused in redistribution of protein daily intake whenlevodopa prescribed. Diet by itself is fundamental for themanagement of each individual person prone to or sufferingfrom IPD. Vegan diets with pulses rich in protein duly balancedwith cereals and supplemented with vitamin B12, reduce theintake of methionine and keep the amount of aromatic aminoacids at a moderate level.